Biological Effects of High Tibial Osteotomy on Spontaneous Osteonecrosis of the Knee. (August 2022) - Kumagai, Ken; Yamada, Shunsuke; Nejima, Shuntaro; Sotozawa, Masaichi; Inaba, Yutaka
Objective: The purpose of this study was to evaluate the postoperative status of spontaneous osteonecrosis of the knee (SONK) after high tibial osteotomy (HTO) with concomitant bone marrow stimulation (BMS) using synovial fluid (SF) biomarkers. Design: Twenty patients with SONK who underwent opening wedge HTO were enrolled. Paired SF samples from the affected knee were collected at the time of HTO surgery and at the time of plate removal. SF concentrations of interleukin (IL)-6, IL-8, and matrix metalloproteinase (MMP)-13 were measured by enzyme-linked immunosorbent assays. The Knee Society Score (KSS) and hip-knee-ankle (HKA) angle were assessed before and 2 years after HTO. Results: The KSS knee and function scores were significantly improved after HTO (mean changes of 33.8 and 29.4, respectively). The mean HKA angle was changed from mechanical varus (−8.6°) to valgus (5.2°). Concentrations of IL-6, IL-8, and MMP-13 were significantly decreased after HTO (mean changes of −73.7%, −32.4%, and −47.9% from preoperative baseline, respectively). Significant correlations were found between lesion size and concentrations of biomarkers, except for preoperative MMP-13. Conclusions: SF levels of biomarkers of inflammation and cartilage degradation were reduced after HTO with a concomitant BMS procedure, suggesting a biological improvement in SONK.